2022
DOI: 10.3390/medicina58111610
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Malnutrition Measured by Hypalbuminemia and Body Mass Index on the Outcome of Geriatric Patients with a Fracture of the Proximal Femur

Abstract: Background and Objectives: Fractures of the proximal femur are a life-changing and life-threatening event for older people. Concomitant malnutrition has been described as an independent risk factor for complications and mortality. Therefore, we examined the influence of albumin and body mass index (BMI) as parameters for the nutritional state on the outcome after geriatric hip fracture surgery. Materials and Methods: Data were retrospectively collected from hospital information systems, and complications and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In addition, vitamin D supplementation in this population has not been associated with a clinically significant improvement in their QoL [ 46 ]. On the contrary, low serum albumin levels have been associated with high mortality [ 38 , 47 ] and postoperative complications [ 48 ] in older patients after hip fracture surgery. An association has also been found between a low lymphocyte count [ 38 ], high neutrophil-to-lymphocyte ratio [ 49 ], and high platelet-to-lymphocyte ratio [ 50 ] with mortality in older patients after hip fractures [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, vitamin D supplementation in this population has not been associated with a clinically significant improvement in their QoL [ 46 ]. On the contrary, low serum albumin levels have been associated with high mortality [ 38 , 47 ] and postoperative complications [ 48 ] in older patients after hip fracture surgery. An association has also been found between a low lymphocyte count [ 38 ], high neutrophil-to-lymphocyte ratio [ 49 ], and high platelet-to-lymphocyte ratio [ 50 ] with mortality in older patients after hip fractures [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported in the literature that hypoalbuminemia is not an independent predictive factor for death and postoperative complications, hypoalbuminemic patients had higher ASA grade and Charlson co‐morbidity index, as well as lower HB and PT. Thus, hypoalbuminemia was also associated with complications and the death of elderly patients 36 . Therefore, we recommend the following for elderly patients: comprehensively evaluate the nutritional risk, enhance the nutritional management and provide nutritional support for elderly patients with femoral neck fractures who have poor nutritional status before surgery; and preoperatively, address severe anemia and postoperative hypoproteinemia to improve postoperative recovery and reduce the likelihood of a poor prognosis for elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…RDW is included in CBC, which is readily available and inexpensive. According to several studies, high RDW levels are closely linked to mortality ( Laulund et al, 2012 , p. 6; Lv et al, 2016 ; Yin et al, 2016 ; Pass et al, 2022 ). A retrospective study of 1574 elderly patients who underwent hip fracture surgery was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RDW is also used to predict the mortality of hip fractures alone or in combination with other factors ( Garbharran et al, 2013 ; Yin et al, 2016 ; Hamdan et al, 2021 ; Marom et al, 2022 ). In numerous studies, low serum albumin levels have been found to negatively correlate with hip fracture mortality ( Pimlott et al, 2011 ; Laulund et al, 2012 ; Pass et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%